The Implementation of Problem-Based Learning to Enhance Students' Discussion Skills in Geography Subject Through Differentiated Learning - Khoirul Huda; Ita Mardiani Zain; Suaibatul Islamiyah (FKIP, Universitas Palangka Raya, 2023)
The independent curriculum has a significant impact on the development of the learning process. Independent curriculum learning prioritizes and prioritizes the needs of students, besides that students are guided to be able to understand the material presented with actual problems that exist in everyday life. The Problem Based Learning learning model is an alternative used by teachers in the learning process. Implementation of Problem Based Learning (PBL) will foster students' ability to discuss with colleagues. Fulfilling the learning needs of students is the main goal of the Independent Curriculum, through differentiated learning can realize the various needs of students in the learning process. This research is a class action research (CAR). This research was conducted for 2 cycles consisting of planning, implementing, observing, and reflecting. The research subjects were students of class X-6 SMA Kemala Bhayangkari 1 Surabaya. This study found that there was an increase in students' discussion skills in cycle 1 and cycle 2. A significant percentage increase in grades was obtained. This increase in value can prove that the application of the problem-based learning model through differentiation learning is able to improve students' discussion skills